Pola interaksi dalam Alquran yang tercermin pada ayat-ayat berbentuk pertanyaan - Ainin, Moh.; Asrori, Imam (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2012)
The Qur’an is a medium of interaction between God and His creatures. This research aims to describe the patterns of interaction in the Qur’an. It employs a qualitative design and content analysis. The results show that the themes of interaction are varied, and the participants of interaction include God and His creatures. The responses in the interaction are categorized into responses based on their origin and those based on the relationship between questions and responses. The motives of interaction vary depending on the context. The background of interaction is divided into physical and non-physical contexts. In addition, the patterns of interaction include one-way and two-way interactions, and the interactional strategies are either direct or indirect.